Preparation and thermal decomposition of solid state cinnamates of alkali earth metals, except beryllium and radium - ZAINA CHIARETTO, Ana Glauce [UNESP]; CARVALHO FILHO, Marco Aurélio da Silva [UNESP]; FERNANDES, Nedja Suely [UNESP]; Ionashiro, Massao [UNESP] (Editora Unesp, 1998)
Foram preparados compostos de fórmula geral ML2.nH2O, onde M é Mg, Ca, Sr e Ba; L é o cinamato (C6H5-CH=CH-COO-) e n = 2; 4; 0,8; 3, respectivamente. A termogravimetria (TG), termogravimetria derivada (DTG), calorimetria exploratória diferencial (DSC) e difratometria de raios-X foram utilizados na caracterização, na verificação da estabilidade térmica e estudo da decomposição térmica desses compostos.

Solid state compounds of general formula ML2.nH2O [where M is Mg, Ca, Sr or Ba; L is cinnamate (C6H5 -CH=CH-COO-) and n = 2, 4, 0.8, 3 respectively], have been synthetized. Thermogravimetry (TG), derivative thermogravimetry (DTG), differential scanning calorimetry (DSC) and X-ray diffraction powder patterns have been used to characterize and to study the thermal stability and thermal decomposition of these compounds.
Preparação e decomposição térmica de cinamatos de metais alcalino-terrosos, exceto berílio e rádio no estado sólido
Keywords: metais alcalino-terrosos; cinamato; decomposição térmica; Alkali earth metals; Cinnamate; Thermal decomposition